Treatment of Canine Multicentric Lymphoma Through Vascular Access Port Versus Peripheral Venous Catheter - Barni, Brunna de Souza; Becerra, José Ricardo Herrera; Vidor, Silvana Bellini; de Oliveira, Mariana Pires; Vieira, Luciane Cristina; Gnoatto, Calvin Braga; Valle, Stella de Faria; Gomes, Cristiano; Gianotti, Giordano Cabral; Contesini, Emerson Antonio (Acta Scientiae Veterinariae, 2020)
Background: Vascular access port (VAP) was developed for the administration of chemotherapeutic agents, minimizing local drug reactions and complications associated with migration of peripheral venous catheter (PVC) in humans. The device is widely used in human oncology and has gained importance in veterinary oncology, especially in long treatment regimens, as in the case of canine lymphoma. VAP favors therapy and the animals’ quality of life. The aim of this study was to describe the use of VAP in dogs, comparing to PVC access, during canine lymphoma chemotherapeutic treatment. Materials, Methods & Results: Eleven dogs with multicentric lymphoma which required chemotherapy were selected for the study. The dogs were randomly allocated to two groups with five and six animals, and each group received the chemotherapy protocol through the PVC (n= 5) or VAP (n= 6). For the sake of standardization, assessments were made whenever the dogs received vincristine sulfate, despite the use of the infusion system in all sessions of the Madison-Wisconsin protocol. A VAP was implanted into the right external jugular vein of six dogs under inhalational anesthesia, using the Seldinger technique. Systolic blood pressure (SBP) levels and handling time during chemotherapy sessions were compared in both groups in three time periods during the procedures: 10 min after arrival to each chemotherapy (P1); immediately after placement of the PVC or puncture of the VAP reservoir (P2); and at the end of chemotherapy (P3). The arithmetic mean of five consecutive assessments was used in each time period. In the chemotherapy sessions, the mean of SBP variation decreased statistically significant in the VAP group compared to PVC group. SBP decreased from P1 to P2 and from P1 to P3 in all sessions (S1, S2, and S3) in the VAP group, and increased in the PVC group. The handling time of VAP group was 110.6 ± 8.4 s, compared to 219.2 ± 24.7 s (mean ± standard error) in the PVC group, showing statistically significant difference (P < 0.001). VAP surgical implantation time averaged 37 min, decreasing gradually from the first (55 min) to the last patient (21 min). Discussion: SBP levels suggest that the VAP group was calmer from the beginning to the end of the sessions, showed lower SBP levels, and required shorter handling time than did the PVC group. Blood pressure is one of the most objective ways to assess welfare or stress in dogs. When dog feels threatened or scared, its body automatically enters a state of emergency and, among several changes, blood pressure increases. VAP surgical implantation in dogs have easy learning, as previously described, proven by implantation time progressive reduction. The Seldinger technique is the method of choice for catheter implantation in humans. Dissection of the jugular vein is an alternative, however, the technique with a single incision and venipuncture is less invasive than its modifications. The jugular vein was used because is the site of choice for central accesses in veterinary practice, with a shorter path to the right atrium and smaller rates of catheter misplacement, reducing the risk of pneumothorax, venous thrombosis, and pinch-off syndrome. VAP surgical implantation in dogs have easy learning, proven by the implantation time progressive reduction. The study confirmed that VAPpromoted animal welfare, shortened chemotherapy sessions, and caused less discomfort to dogs treated for multicentric lymphoma, as indicated by the reduction in SBP, when compared to the PVC group.